Bridging the Service Gap - Business Process Redesign & Information Technology as Multidimensional Success Driver for Logistics Service Providers - Martin Göbl; Markus Klaus (Journal of Applied Leadership and Management, 2014)
Research questions: Attaining competitive advantages is a result of satisfying customer demands with a certain service/product composition. The business process model approach has become popular in order to meet service needs. In addition more and more companies create value along supply chains and the function of logistics becomes part of such a value creation. Collaboration is one major influencing success factor. By adjusting to market changes companies focus on internal processes and costs instead of targeting on customer and supply chain total benefits/costs and especially quality chances. Restructuring business processes therefore is estimated to be under evaluated. IT hereby shows a manifold impact. This value is analyzed and conducted on an ongoing business process redesign project of a logistics service provider (LSP). Methods: The theoretical part of the paper illustrates the framework of business processes, evaluation, development of redesign techniques and strategies by linking this background to the role of IT with focus on a customer service process. In a second step an equitation model evaluates hypotheses from a LSP and customer perspective in order to formulate innovation potentials targeting the customer collaboration process.Results: The findings express the need to overcome company borders in supply chains, include partners and use IT tools to develop information quality to raise a final higher customer satisfaction. Companies rely more and more on their networks, while cost and business process programs dont include relationship and process gains. Especially the impact of rising information quality in the supply chain gives the possibility to evaluate and raise quality developments.
Keywords: 650